1995
DOI: 10.1007/bf00209497
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of gene mutations among 32 unrelated Japanese Gaucher disease patients: absence of the common Jewish 84GG and 1226G mutations

Abstract: The prevalence of seven different mutations (84GG, IVS2 + 1, 754A, 1226G, 1342C, 1448C, and 1504T) was investigated in 32 unrelated Japanese Gaucher patients of which 20 were type I, 6 were type II, and 6 were type III). These mutations constitute 95% of the mutations observed in Jewish patients with Gaucher disease and 75% of the mutations in non-Jews (European). The most frequent mutation, 1448C (L444P), accounted for 26 alleles (40.6%); the second most prevalent mutation was 754A (F213I), accounting for 7 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0
1

Year Published

1997
1997
2001
2001

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 14 publications
2
40
0
1
Order By: Relevance
“…In Jewish and non-Jewish Caucasian populations, the N370S (cDNA 1226G) GC mutation is the most prevalent (Amaral et al, 1993;Horowitz and Zimran, 1994;Lacerda et al, 1994a), causing synthesis of a catalytically abnormal enzyme (Grace et al, 1990;Ohashi et al, 1991;van Weely et al, 1993). This mutation has so far not been encountered in the Japanese population (Ida et al, 1995). The L444P (cDNA 1448C) GC mutation is relatively frequent in the Jewish and non-Jewish Caucasian populations and in Japanese populations Ida et al, 1995) and leads to synthesis of glucocerebrosidase, which is rapidly degraded (Grace et al, 1991;Ohashi et al, 1991;Grace et al, 1994).…”
mentioning
confidence: 95%
“…In Jewish and non-Jewish Caucasian populations, the N370S (cDNA 1226G) GC mutation is the most prevalent (Amaral et al, 1993;Horowitz and Zimran, 1994;Lacerda et al, 1994a), causing synthesis of a catalytically abnormal enzyme (Grace et al, 1990;Ohashi et al, 1991;van Weely et al, 1993). This mutation has so far not been encountered in the Japanese population (Ida et al, 1995). The L444P (cDNA 1448C) GC mutation is relatively frequent in the Jewish and non-Jewish Caucasian populations and in Japanese populations Ida et al, 1995) and leads to synthesis of glucocerebrosidase, which is rapidly degraded (Grace et al, 1991;Ohashi et al, 1991;Grace et al, 1994).…”
mentioning
confidence: 95%
“…In our genetic study, the 754A mutation was identified; it is the second-most-common mutation in Japanese patients. 15 Previous studies documented only one 754A allele in a variant type 1 in a patient with non-Jewish English ancestry. 12 The 754A mutation is moderately associated with a neuropathic form of Gaucher's disease; however, this mutated allele was also identified in nonneuropathic forms.…”
Section: Acta Cytologicamentioning
confidence: 99%
“…3,4 The great majority of alleles that cause Gaucher's disease in the Jewish population have been identified. [2][3][4] However, Ida et al 15 reported that the mutant alleles identified in the Japanese population are different from those observed in Jewish and non-Jewish European patients with Gaucher's disease.…”
mentioning
confidence: 99%
“…Some correlation between genotypes and phenotypes has been reported (2,13,18). For example, the 1226G mutation (a G to A transition at nucleotide 5841, leading to the substitution of serine for aspargine at residue 370), which is commonin Jewish but absent in Japanese patients (12), tends to be linked to a very mild phenotype (13,18). Nearly 90% of the patients homozygousfor 1226Ghave a very mild clinical course or are sometimesasymptomatic, so that this mutation is knownas a "protective mutation" (4,13,18).…”
Section: Discussionmentioning
confidence: 99%